Correlation between Emission-line Luminosity and Gamma-Ray Dominance in the Blazar 3C 279 - A. Dmytriiev; M. Böttcher; T. O. Machipi (The Astrophysical Journal, 2023)
Despite numerous studies, the origin of the γ -ray emission from blazars is still debated, in particular whether it is produced by leptonic or hadronic processes. In this study, we are testing the leptonic scenario for the flat-spectrum radio quasar 3C 279, assuming that the γ -ray emission is generated by inverse Compton scattering of external target photons from the broad-line region (IC-BLR scenario). For this purpose we use a 10 yr data set of the source consisting of the optical spectroscopy data from the Steward Observatory blazar monitoring program and Fermi Large Area Telescope γ -ray data. We search for a possible correlation between the Compton dominance and the emission-line luminosity using the discrete correlation function analysis. As a result, we find no significant correlation between these two quantities at any time lag value, while the emission-line luminosity displays a moderate correlation with the γ -ray flux at a zero time lag. We also reveal that the optical synchrotron continuum flux shows a pronounced correlation with the γ -ray flux, and therefore we interpret these results within the leptonic IC-BLR scenario where the variations in Compton dominance are primarily induced by changes in the magnetic field, rather than in the emission-line luminosity.